Communication pattern between nurses and elderly patients through a neuro-linguistic programming approach - Rustan, Edhy; Hasriani, Hasriani (Jurnal Studi Komunikasi, 2020)
This study aimed to determine the pattern of communication between nurses and elderly patients towards a healthy lifestyle through the NLP approach. It was a qualitative study using a case study method involving 6 nurses and 15 elderly patients active in Prolanis activities in Batu Ke'de village, Masalle subdistrict. The results of observations and interviews were then analysed using interactive analysis techniques from Miles and Huberman. Based on the results of observation and analysis, the study found that nurses could use the neurolinguistic programming method in communicating with the elderly which causes changes in the thinking and behaviour patterns of the elderly towards a healthy lifestyle. Therefore, the NLP method can be used by nurses as one method of communicating and influencing elderly patients by taking into account its four main pillars, which are the outcome, rapport, sensory acuity, and flexibility